2021
DOI: 10.3390/antiox10050716
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal-Dependent Glycative Stress Is Prevented by the Natural Antioxidant Oleuropein in Human Dental Pulp Stem Cells through Nrf2/Glo1 Pathway

Abstract: Methylglyoxal (MG) is a potent precursor of glycative stress (abnormal accumulation of advanced glycation end products, AGEs), a relevant condition underpinning the etiology of several diseases, including those of the oral cave. At present, synthetic agents able to trap MG are known; however, they have never been approved for clinical use because of their severe side effects. Hence, the search of bioactive natural scavengers remains a sector of strong research interest. Here, we investigated whether and how ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 70 publications
2
38
0
Order By: Relevance
“…Next, we investigated the effect of GOLD on the expression of NRF2 and GLO1 in mesangial cells. The NRF2/GLO1 signaling system is an important antioxidant activity signaling system [ 21 , 30 ]. As shown in Figure 4 A,C, GOLD significantly inhibited the expression of NRF2 and GLO1 in mesangial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we investigated the effect of GOLD on the expression of NRF2 and GLO1 in mesangial cells. The NRF2/GLO1 signaling system is an important antioxidant activity signaling system [ 21 , 30 ]. As shown in Figure 4 A,C, GOLD significantly inhibited the expression of NRF2 and GLO1 in mesangial cells.…”
Section: Resultsmentioning
confidence: 99%
“…NRF2 is a key transcription factor that regulates genes involved in the antioxidant defense system. The expression of homeostasis regulators such as glyoxalase 1 (GLO1), which are regulated by NRF2, plays a role in preventing renal lesions from excessive inflammatory reactions through antioxidant reactions in mesangial cells [ 21 ]. NRF2 remains inactive while binding to Kelch-like ECH-associated protein 1 (KEAP1) in the cytoplasm [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In both crown and root dentin, we found a significant increase of MGO-derived AGEs in the >50yo group compared to <26yo patients ( Figure 1E ; p<0.05). Previous research has shown that MGO-derived AGEs accumulate in both the dental pulp and periodontal tissues (Retamal et al 2016; Delle Monache et al 2021), thus it is likely that perfusion from these tissues may promote MGO formation in dentin over time. Unlike bone, dentin has no turnover which facilitates the accumulation of AGEs in its organic matrix, similar to other slow turnover tissues such as tendons (Birch 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The thermal cycling conditions were 1 cycle at 95 °C for 5 min followed by 45 cycles at 95 °C for 20 s and 60 °C for 30 s. Melting curves were performed for all of the primer pairs in standard conditions. Comparative analysis of gene expression was performed by means of the 2−(∆∆ C T) method [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%